Long-term disability and prognostic factors in polyneuropathy associated with anti-myelin-associated glycoprotein (MAG) antibodies. (4th May 2017) - Galassi, Giuliana; Tondelli, Manuela; Ariatti, Alessandra; Benuzzi, Francesca; Nichelli, Paolo; Valzania, Franco
Abstract : Aim of the study: Neuropathy associated with IgM monoclonal gammopathy (MGUS) represents distinctive clinical syndrome, characterized by male predominance, late age of onset, slow progression, predominantly sensory symptoms, deep sensory loss, ataxia, minor motor impairment. More than 50% of patients with neuropathy-associated MGUS possess antibodies against myelin-associated glycoprotein (MAG). Purpose of our study was to assess effects on disease progression of demographic, clinical and neurophysiological variables in our large cohort of patients. Materials and Methods: Forty-three Caucasians patients were followed every eight months for median duration time of 93 months. Extremity strength was assessed with Medical Research Council (MRC) Scale, disability with overall disability status scale (ODSS), modified Rankin Scale and sensory function with Inflammatory Neuropathy Cause and Treatment (INCAT) sensory scale (ISS). Statistical analyses were conducted with parametric or non-parametric measures as appropriate. Survival analysis was used to test predictive value of clinical, demographical and neurophysiological variables. Variance analysis was conducted to explain difference on MRC between patients and groups at different time from onset. Results: Results showed that demyelinating pattern, older age and absence of treatment were significant risk factors for disability worsening. No other factors emerged as predictors including gender, ataxia and tremor at baseline, level of anti-MAG and IgM protein concentration in serum. Despite worsening of all outcome measures between first and last visit, quality of life (HRQol) judged by patients did not vary significantly. Conclusions: Our study provides evidence that electrophysiologic pattern, age of onset and absence of treatment are strong predictor of prognosis in anti-MAG polyneuropathy.